Industry Analysis: Apple Processors in the Northeastern U.S. - Kristin L. Rowles (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2001)
Apple processors are an important link in the marketing chain from apple growers to consumers, and their perspective is critical in understanding the industry's situation and projecting the industry's future. This paper reports the results of a survey of Northeastern U.S. apple processors. The survey was conducted to provide a snapshot of current strategic issues in the industry, to assess the industry's strengths and weaknesses, to identify opportunities and threats, to forecast future trends, and to provide background data for additional research in this industry. The survey results provide an overview of trends, issues, and processor perspectives in the Northeastern apple processing industry. The outlook of many processors for future of the industry is negative or uncertain. Processors' concerns reflect many of those held by the industry's apple growers. The processing sector faces a number of challenges in a rapidly changing and globalizing market. Looking forward, the industry must consider how to make its products relevant in current and future markets and how to compete effectively with global rivals. Although the outlook of many respondents was negative or uncertain, the survey responses also reveal several industry strengths and opportunities. This survey was completed as a part of a larger research project focused on the Northeastern apple processing industry. The final project results will identify and analyze marketing strategies and opportunities in the industry. The research will convey important data about consumer trends relevant to the processed apple industry, and this data will be interpreted in the context of the industry's current situation. The information collected should be useful to growers and processors in assessing future opportunities and enhancing competitive capabilities in their efforts to strengthen this important sector of the regional apple industry.
Keywords: 330; Verarbeitung von Obst und Gemüse; Apfel; USA <Nordoststaaten>